Kindergarten teachers' knowledge of the initial indicators of autism spectrum disorder - Mukhtar, Frah Ekram; Khishaim, Salwa Mustafa (Journal of Educational and Psychological Sciences, 2023)
This study aimed at identify the extent to which kindergarten teachers know the initial indicators of autism spectrum disorder in the city of Jeddah, this study used the descriptive approach to achieve its goals, by designing a tool that included (22) divided phrases On my dimension (indicators of communication and social interaction, indicators of stereotypical behaviors and specific interests), the number of the participating sample reached (273) kindergarten teachers in Jeddah, The results of this study showed a high level of knowledge of kindergarten teachers of the initial indicators of autism spectrum disorder, in addition to the absence of statistically significant differences due to the variable of previous work experience with children with autism spectrum disorder, and the researcher recommends including curricula in the faculties of preparing kindergarten teachers on early detection and intervention courses, and working on holding specialized training workshops in the field of early intervention to increase the background of kindergarten teachers in the field of special education and dealing with people with disabilities, and strategies Education that helps develop skills in the event of signs of developmental delay in children.
Keywords: Autism Spectrum Disorder; Kindergarten Teachers; Primary Indicators of Autism Spectrum Disorder